KONTRIBUSI KEKUATAN OTOT LENGAN DAN KELINCAHAN DENGAN KEMAMPUAN TANGKAPAN SATU KAKI CABANG OLAHRAGA GULAT MAHASISWA PRODI PENJASKESREK STKIP YPUP MAKASSAR - Jahrir, Andi Sahrul; Yusuf, Akbar (Jurnal Penjaskesrek, 2018)
This study aims to determine the contribution of arm muscle strength and speed with the ability of one-foot catch in wrestling sports for students of Penjaskesrek study program STKIP YPUP Makassar. The research method used is descriptive using a sample of 30 students who have programmed wrestling courses. The results of this study this study showed the contribution of arm muscle strength with the ability of one foot catch and the contribution of speed with the ability of one foot catch and the contribution between arm muscle strength and speed with the ability to catch one leg of Penjaskesrek Study Program students STKIP YPUP Makassar